Laryngotracheoesophageal Cleft Type IV in a Preterm Neonate. A Case Report and Literature Review - Sokou, Rozeta; Batsiou, Anastasia; Konstantinidi, Aikaterini; Kopanou-Taliaka, Paschalia; Tsaousi, Marina; Lampridou, Maria; Tavoulari, Evangelia-Filothei; Mitropoulos, Konstantinos; Liakou, Paraskevi; Willadara-Gamage, Stamatina; Vlastarakos, Petros V; Iliodromiti, Zoi; et al. (Prague medical report, 2024)
We present a case of a preterm neonate with a type IV laryngo-tracheo-oesophageal cleft, an uncommon congenital malformation, resulting from the failure of separation of the trachea and the oesophagus during fetal development, often associated with other deformities as well. Data in the literature shows that the long-term morbidity from the entity has declined over the last decades, even though prognosis remains unfavourable for types III and IV. This report emphasizes the complex issues neonatologists are faced with, when treating neonates with this rare disorder in the first days of life, what will raise suspicion of this rare medical entity, and that direct laryngoscopy/bronchoscopy finally depicts the exact extension of the medical condition. At the same time extensive evaluation for coexisting congenital anomalies should be performed. For all the above reasons, these neonates should be treated in specialized tertiary pediatric centers for multidisciplinary prompt management, which may improve, the outcome.
Keywords: laryngoskopie; dítě; Esophagus; lidé; ezofágus; Larynx; Trachea; Child; Congenital Abnormalities; trachea; novorozenec; Infant, Newborn; Humans; vrozené vady; Laryngoscopy; larynx